Mapping of Mycobacterium tuberculosis katG Promoters and Their Differential Expression in Infected Macrophages - Master, Sharon (American Society for Microbiology, 2001)
Intracellular pathogenic bacteria, including Mycobacterium tuberculosis, frequently have multitiered defense mechanisms ensuring their survival in host phagocytic cells. One such defense determinant in M. tuberculosis is the katG gene, which encodes an enzyme with catalase, peroxidase, and peroxynitritase activities. KatG is considered to be important for protection against reactive oxygen and nitrogen intermediates produced by phagocytic cells. However, KatG also activates the front-line antituberculosis drug isoniazid, hence rendering M. tuberculosis exquisitely sensitive to this compound. In this context, katG expression represents a double-edged sword, as it is an important virulence determinant but at the same time its activity levels determine sensitivity to INH. Thus, it is important to delineate the regulation and expression of katG, as this not only can aid understanding of how M. tuberculosis survives and persists in the host but also may provide information of relevance for better management of INH therapy. Here, we report the first extensive analysis of the katG promoter activity examined both in vitro and in vivo. Using S1 nuclease protection analysis, we mapped the katG mRNA 5′ ends and demonstrated that two promoters, P(1)furA and P(1)katG, control transcription of katG. The furA and katG genes are cotranscribed from P(1)furA. Both P(1)furA and P(1)katG promoters show induction upon challenge with hydrogen peroxide and cumene hydroperoxide. Studies carried out using the transcriptional fusions P(1)furA-gfp, P(1)katG-gfp, and P(1)furA-P(1)katG-gfp confirmed the existence of two katG promoters. In addition, we showed that both promoters are expressed in vivo during intracellular growth of virulent M. tuberculosis H37Rv. P(1)furA is induced early upon infection, and P(1)katG becomes active only upon extended growth in macrophages. These studies delineate the transcriptional organization of the furA-katG region and indicate differential regulation in vivo of the two katG promoters. These phenomena most likely reflect the differing demands at sequential stages of the infection cycle and may provide information for improved understanding of host-pathogen interactions in tuberculosis and for further optimization of INH chemotherapy.